Benign solidification of molten slag on rotary cup atomizer: slag shell formation, remelting and residue characteristics - Yiwen Lv; Maolin Dai; Junjun Wu; Hong Wang; Yudong Ding; Min Cheng; Xun Zhu; Qiang Liao (Waste Management, 2026)

Challenges of high temperature on ultrasonic propagation in coal reservoirs: Insights from moisture desorption and fissure expansion - Junjun Feng; Shigeng Li; Yankun Ma; Yuanfang Qu; Qisong Huang; Houcheng Ding (Gas Science and Engineering, 2025)

Solvent-free green preparation of PVDF/ PPTA-pulp hollow fiber membrane and construction of the multi-porous structure - Haolong Xue; Junjun Sun; Dawei Ji; Zhengjie Yue; Xiaocao Zhao; Yizhe Ding; Huiru Zheng; Changfa Xiao (Chemical Engineering Journal, 2025)

Durability and degradation mechanisms of dredged clays stabilized with ternary geopolymer under cyclic drying-wetting environments - Jianhua Wang; Yongfeng Deng; Cong Mou; Jianwen Ding; Junjun Ni; Xing Wan (Bulletin of Engineering Geology and the Environment, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Mixed vineyard prunings and sheep manure compost: Creating changes in vineyard soil dominant microbiota to impact fruit quality - Qian Tu; Yuanyuan Li; Weikang Ding; Shubo Zhou; Yanping Huang; Shiqiu Liu; Xuwu Min; Jiarui Zhang; Junjun Li; Chunlong Yuan (Applied Soil Ecology, 2025)

Redefining limits: Impact of nozzle diameter on film flow and atomization beyond the synchronizing radius - Yu Tan; Xudong Chen; Maojiang Jia; Bin Ding; Junjun Wu; Yuelin Qin (Chemical Engineering Journal, 2025)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Biological culture module for plant research from seed-to-seed on the Chinese Space Station - Chaoxian Jia; Weibo Zheng; Fangwu Liu; Kun Ding; Yongchun Yuan; Junjun Wang; Dazhao Xu; Tao Zhang; Huiqiong Zheng (Life Sciences in Space Research, 2024)

Clusterin is a Potential Therapeutic Target in Alzheimer’s Disease - Nazhakaiti Palihati; Yuanhong Tang; Yajuan Yin; Ding Yu; Gang Liu; Zhenzhen Quan; Junjun Ni; Yan Yan; Hong Qing (Molecular Neurobiology, 2024)

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Investigation on performance improvement of dredged sediment with high water content stabilized with alkali-activated materials - Jianhua Wang; Heng Wang; Jianwen Ding; Junjun Ni; Cong Mou; Xing Wan (Journal of Soils and Sediments, 2024)

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Recombinant HBsAg-S and RFRP-3 DNA vaccine promotes reproduction hormone secretion in sheep - Yi Ding; Xunping Jiang; Haijing Jing; Guiqiong Liu; Junjun Cheng (Theriogenology, 2023)

Structural and functional MRI evidence for significant contribution of precentral gyrus to flexible oculomotor control: evidence from the antisaccade task - Zhenlan Jin; Dong-gang Jin; Min Xiao; Aolin Ding; Jing Tian; Junjun Zhang; Ling Li (Brain Structure and Function, 2022)
Antisaccade task requires inhibition of a prepotent prosaccade to a peripheral target and initiation of a saccade to the opposite location, and, therefore, is used as a tool to investigate behavioral adjustment. The frontal and parietal cortices are both known for their activation during saccade generation, but it is unclear whether their neuroanatomical characteristics also contribute to antisaccades. Here, we took antisaccade cost (antisaccade latency minus prosaccade latency) as an index for additional time for generating antisaccades. Fifty-eight participants conducted pro and antisaccade tasks outside the magnetic resonance imaging (MRI) scanner and their structural MRI (sMRI) data were also collected to explore brain regions neuroanatomically related to antisaccade cost. Then, twelve participants performed saccade tasks in the scanner and their task-state functional MRI (fMRI) data were collected to verify the activation of structurally identified brain regions during the saccade generation. Voxel-based morphometry (VBM) results revealed that gray matter volume (GMV) of the left precentral gyrus and the left insula were positively correlated with the antisaccade cost, which was validated by the prediction analysis. Brain activation results showed the activation of the precentral during both pro and antisaccade execution period, but not the insula. Our results suggest that precentral gyrus and insula play vital roles to antisaccade cost, but possibly in different ways. The insula, a key node of the salience network, possibly regulates the saliency processing of the target, while the precentral gyrus possibly mediates the generation of saccades. Our study especially highlights an outstanding role of the precentral gyrus in flexible oculomotor control.

Alleviation of the detrimental effect of water deficit on wheat (Triticum aestivum L.) growth by an indole acetic acid-producing endophytic fungus - Xiaojing Qiang; Junjun Ding; Wei Lin; Qiaozhen Li; Chunying Xu; Qian Zheng; Yuzhong Li (Plant and Soil, 2019)

Microbial responses to inorganic nutrient amendment overridden by warming: Consequences on soil carbon stability - Mengmeng Wang; Junjun Ding; Bo Sun; Junyu Zhang; Kristen N. Wyckoff; Haowei Yue; Mengxin Zhao; Yuting Liang; Xiaoyue Wang; Chongqing Wen; Jizhong Zhou; Yunfeng Yang (Environmental Microbiology, 2018)
Summary Eutrophication and climate warming, induced by anthropogenic activities, are simultaneously occurring worldwide and jointly affecting soil carbon stability. Therefore, it is of great interest to examine whether and how they interactively affect soil microbial community, a major soil carbon driver. Here, we showed that climate warming, simulated by southward transferring Mollisol soil in agricultural ecosystems from the cold temperate climate zone (N) to warm temperate climate (C) and subtropical climate zone (S), decreased soil organic matter (SOM) by 6%–12%. In contrast, amendment with nitrogen, phosphorus and potassium enhanced plant biomass by 97% and SOM by 6% at the N site, thus stimulating copiotrophic taxa but reducing oligotrophic taxa in relative abundance. However, microbial responses to nutrient amendment were overridden by soil transfer in that nutrient amendment had little effect at the C site but increased recalcitrant carbon‐degrading fungal Agaricomycetes and Microbotryomycetes taxa derived from Basidiomycota by 4‐17 folds and recalcitrant carbon‐degrading genes by 23%–40% at the S site, implying a possible priming effect. Consequently, SOM at the S site was not increased by nutrient amendment despite increased plant biomass by 108%. Collectively, we demonstrate that soil transfer to warmer regions overrides microbial responses to nutrient amendment and weakens soil carbon sequestration.

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Land scale biogeography of arsenic biotransformation genes in estuarine wetland - Si‐Yu Zhang; Jian‐Qiang Su; Guo‐Xin Sun; Yunfeng Yang; Yi Zhao; Junjun Ding; Yong‐Shan Chen; Yu Shen; Guibing Zhu; Christopher Rensing; Yong‐Guan Zhu (Environmental Microbiology, 2017)
Summary As an analogue of phosphorus, arsenic (As) has a biogeochemical cycle coupled closely with other key elements on the Earth, such as iron, sulfate and phosphate. It has been documented that microbial genes associated with As biotransformation are widely present in As‐rich environments. Nonetheless, their presence in natural environment with low As levels remains unclear. To address this issue, we investigated the abundance levels and diversities of aioA , arrA , arsC and arsM genes in estuarine sediments at low As levels across Southeastern China to uncover biogeographic patterns at a large spatial scale. Unexpectedly, genes involved in As biotransformation were characterized by high abundance and diversity. The functional microbial communities showed a significant decrease in similarity along the geographic distance, with higher turnover rates than taxonomic microbial communities based on the similarities of 16S rRNA genes. Further investigation with niche‐based models showed that deterministic processes played primary roles in shaping both functional and taxonomic microbial communities. Temperature, pH, total nitrogen concentration, carbon/nitrogen ratio and ferric iron concentration rather than As content in these sediments were significantly linked to functional microbial communities, while sediment temperature and pH were linked to taxonomic microbial communities. We proposed several possible mechanisms to explain these results.

Carnosic acid protects non-alcoholic fatty liver-induced dopaminergic neuron injury in rats - Ting Xu; Junjun Zhou; Jie Zhu; Shuai Zhang; Ning Zhang; Yan Zhao; Chunchun Ding; Xue Shi; Jihong Yao (Metabolic Brain Disease, 2017)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Heterologous expression and characterization of a malathion-hydrolyzing carboxylesterase from a thermophilic bacterium, Alicyclobacillus tengchongensis - Zhenrong Xie; Bo Xu; Junmei Ding; Lingyun Liu; Xuelin Zhang; Junjun Li; Zunxi Huang (Biotechnology Letters, 2013)